EUROPEAN ACCREDITATION AGENCY’S VIEW ON KAZAKHSTAN’S ENGINEERING AND INFORMATION TECHNOLOGY HIGHER EDUCATION - Ahrens, Andreas; Foerster, Martin; Zascerinska, Jelena; Wasser, Iring (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In the era of digital economy, there is an urgent need in highly qualified engineering and Information Technology (IT) specialists in Kazakhstan. The aim of the research is to analyse the needs of higher education in the field of engineering and IT in Kazakhstan underpinning elaboration of implications for higher education in the field of engineering and IT in Kazakhstan. The empirical study was carried out in October 2019. Exploratory study was implemented. Interpretive paradigm was employed in the present work. Non-structured interview served as the basis for data collection. Content analysis was performed for data analysis. Findings of theoretical analysis allow extending three-component model on needs analysis, namely experts’ perspective, educators’ perspective, and students’ perspective by the fourth component, namely community perspective. Implications for higher education in Kazakhstan are formulated as following: universities delivering higher education in the field of engineering and IT in Kazakhstan need to balance academic and practical components in their study programmes; interaction between educators and students, on the one side, as well as enterprises, companies and industry, on the other side, should be enhanced in higher education in the field of engineering and IT in Kazakhstan. Directions of future work are proposed.